Comparison of different fixation and staining techniques on sperm morphometry and morphology in the Florida manatee - Jonathan R. Cowart; Sofia N. Danford; Danielle M. Collins; Briana-Lee Schaffner; Connor Kelligrew; Iskande V. Larkin (Theriogenology Wild)
Computer-aided sperm morphology analysis (CASMA) is quickly becoming the industry standard for objective morphometric analysis of sperm. For efficient and accurate sperm analysis via CASMA, species-specific optimization of fixation and staining techniques is necessary. This is especially true for novel species, such as marine mammals, where information regarding the spermatozoon is significantly limited. Adding to the growing knowledge of marine mammal sperm, this study investigated the effects that different fixatives and stains had on sperm head morphometry and morphology of Florida manatee (Trichechus manatus latirostris) sperm. Sperm were collected postmortem from four recently deceased Florida manatees and fixed in one of three different fixatives: Formalin 10 Equine Semen Diluent, 2.5 % glutaraldehyde in 0.1 M sodium cacodylate buffer, or 4 % paraformaldehyde. Sperm were then stained using one of four different stains: SpermBlue®, Quick III™, Hemacolor™, or Coomassie blue. A total of 200 sperm from each manatee were analyzed for each fixative:stain combination using the Sperm Class Analyzer® computer-aided sperm analysis (CASA) system for the eight standard head morphometric parameters. Sperm morphology was assessed visually using brightfield microscopy for different morphological abnormalities. Both fixation and staining independently had significant effects on sperm head size and shape when compared across all treatments. As the true morphometry of unfixed and unstained Florida manatee sperm is still unknown, it is unable to be determined which fixative:stain combination imposes the least effect on sperm head morphometry and is thus optimal for the analysis of Florida manatee sperm using CASMA. Opportunistic field sampling of marine mammal sperm imposes logistical constraints which may limit the ability to compare methodologies utilizing different fixatives and staining combinations. Continued research is needed for optimization and standardization of sperm processing, fixation, staining, and analysis of Florida manatee sperm as well as sperm from other marine mammal species.